METHODS FOR STIMULATION OF AUTOMOTIVE MARKET IN CURRENT ECONOMIC CONDITIONS - L. Alimova (Вестник университета, 2018)
The main ways to stimulate demand in the automotive market are examined. The types of state programs and concessional lending, conditions for participation in them and also to whom they are distributed are listed. Statistical data on the results of government support for 2016-2017 are presented. Support programs from automakers and efficiency from their application are indicated. New conditions of state support from the Government of the Russian Federation and the main growth zones for the current period are noted.